Land use Planning for the Nilgiris: Part II- Classification of Land Utilization - Basu, J K; Narayanaswamy, S; Rege, N D (Journal of Soil and Water Conservation, 2022)
Land Use planning is the essential pre- requisite for conservation farming which is designed to make the best use of land and to preserve the soil and maintain, at the same time, its productivity on a permanent basis. Basu3, in his presidential address delivered at the Survey and Plan- ning Section at the Second Annual General Meeting of the Soil Conservation Society of India, while emphasizing this fact, recom- mended that necessary survey and land-use planning should be undertaken in some parts of Indian Union, so that the drawbacks and the ill-effects of the present system of land utilization may be gauged; and with the clue available then a standard pattern of the most economic and appropriate land-use classes may be devised. Campbe112 states that the modern concept of land conservation is Wise use of land according to its capacity to produce, rather than the need to handle damaging runoff and erosion terracing, dams, gully plugging, basin listing, etc." He further states that appropriate land utilization aims at restoring the natural biological balance to the land and making it c’ a sound economic unit at the same time attending to the requirements of the farmers and the capacity of the land.